2020
DOI: 10.1002/cssc.202001372
|View full text |Cite
|
Sign up to set email alerts
|

Flow Chemistry for Cycloaddition Reactions

Abstract: Continuous flow reactors form part of a rapidly growing research area that has changed the way synthetic chemistry is performed not only in academia but also at the industrial level. This Review highlights the most recent advances in cycloaddition reactions performed in flow systems. Cycloadditions are atom-efficient transformations for the synthesis of carbo-and heterocycles, involved in the construction of challenging skeletons of complex molecules. The main advantages of translating these processes into flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 271 publications
(330 reference statements)
0
13
0
Order By: Relevance
“…[7b] With regards to cycloaddition reactions, several examples using flow techniques are reported in the literature. [8] A variety of different Diels-Alder reactions was investigated in flow. [9] Hornung et al reported on the investigation and up-scaling of the Diels-Alder reaction of myrcene with acrylic acid in two different types of flow reactors, a tubular and a plate-type, and compared it to a batch stirred tank, and achieved shorter reaction times as well as a more uniform reaction using the flow technique.…”
Section: Introductionmentioning
confidence: 99%
“…[7b] With regards to cycloaddition reactions, several examples using flow techniques are reported in the literature. [8] A variety of different Diels-Alder reactions was investigated in flow. [9] Hornung et al reported on the investigation and up-scaling of the Diels-Alder reaction of myrcene with acrylic acid in two different types of flow reactors, a tubular and a plate-type, and compared it to a batch stirred tank, and achieved shorter reaction times as well as a more uniform reaction using the flow technique.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) ; Cambié et al. (2016) ; Sambiagio and Noël (2020) 22 Asymmetric synthesis Ötvös and Kappe (2021) 23 Cycloaddition reactions García-Lacuna et al. (2020) 24 Integration of flow chemistry with 3D-printing technologies Sans (2020) 25 Circular synthesis to material manufacturing Sivo et al.…”
Section: Importance Of Flow Chemistrymentioning
confidence: 99%
“…One approach to developing safe 21 and readily scalable procedures for chemistries involving unstable intermediates and intense conditions is flow chemistry. [22][23][24][25][26] This approach has been successfully applied to heterocycle synthesis, 27-28 cycloadditions [29][30] and even to acyl ketene formation, 31 and recent developments continue to show the potential flexibility 32 and portability 33 of this approach. Flow chemistry is often greener 34 than batch chemistry, and sometimes allows access to transformations near impossible 35 under batch conditions.…”
Section: © Author(s)mentioning
confidence: 99%